Indices of over-reaching following intensified training: role of carbohydrate intake - Snyder, A. C.; Kuipers, H.; Cheng, B.; Servais, R.; Fransen, E. (Medicine & Science in Sports & Exercise, 1993)
The purpose of this study was to determine if consumption of appropriate amounts of carbohydrate during a period of increased exercise training would protect against becoming over-reached (overtrained). Cyclists (M = 8) were measured during three training periods: (a) normal (moderate intensity, long duration, 7 days), (b) overtraining (high intensity, 15 days), and (c) recovery (minimal training, 6 days). Carbohydrate ingestion was similar, between 60 and 70 percent at all times. Markers for overtraining were: (a) work maximum, (b) HRmax, (c) HLa:RPE, (d) cortisol, and (e) responses to a questionnaire. All subjects had at least four of the five indicators of over-reaching but no variation in muscle glycogen levels. Implication: Overtraining (over-reaching) occurs independent of muscle glycogen levels.